Political Power and Tribalism in Kenya - Shilaho, Westen K. (Springer International Publishing, 2018)
This book discusses Kenya's transition from authoritarianism to more democratic forms of politics and its impact on Kenya's multi-ethnic society. The author examines two significant questions: Why and how is ethnicity salient in Kenya's transition from one-party rule to multiparty politics? What is the relationship between ethnic conflict and political liberalization? The project explains the perennial issues of political disorganization through state violence and ethnicization of politics, and considers the significance of the concept of justice in Kenya.